Fauna de Aedes (Ochlerotatus) scapularis e as alterações ambientais provocadas pela construção das barragens das usinas hidrelétricas Capim Branco I e Capim Branco II, no Rio Araguari, no Município de Uberlândia, Minas Gerais - Brasil - Vieira, Glaucimar Soares da Silva (2007)
With the construction of two hydroelectric power plants in the lower level of Araguari river Capim Branco I and Capim Branco II , we had the opportunity to study the fauna of Ae. (Och.) scapularis in those areas, before and after the environmental alterations provoked by the construction. The study was carried out from May 2003 to April 2005, at the same time in the two areas. In the area of construction of the barrage of Capim Branco I the environmental alterations began in May 2004, while in Capim Branco II they occurred in March 2005. Four fixed points were chosen for capture of the insects being two in the area of construction of the barrage of Capim Branco I (one to the edge of Araguari river and the other 184m further up on a higher topographical position) and two in Capim Branco II (one to the edge of Araguari river and the other 584m up on a higher topographical position). This work has for objective the study of the fauna of Ae. (Och.) scapularis being taken into consideration the physiographical characteristics of the areas. There have been a total of 96 field collections being 64 of 3:00 hours each and 32 of 12:00 hours each. Shannon traps were used and in the captures of 12:00 hours with three CDC-type traps being used. However these last ones were not well succeeded. An ecological profile for each area was elaborated in order to study and describe their environment. A total of 61 samples of Ae. (Och.) scapularis were captured in the two areas. In the first stage 90.57% of the insects were captured in the area of construction of the barrage of Capim Branco II and 9.43% in the area of Capim Branco I. During the second stage 87.50% were captured in the area of construction of the barrage of Capim Branco I and 12.50% in the area of Capim Branco II. With the obtained data it was observed that the area of construction of the barrage of Capim Branco II is more favorable to the fauna of Ae. (Och.) scapularis than Capim Branco I. The environmental alterations provoked by the construction of the barrages of Capim Branco I and Capim Branco II were related to the suppression of vegetation, the great circulation of vehicles and machinery, intense noise, dust and workers' presence in the work place. We consider that there was no alteration in the fauna of Ae. (Och.) scapularis during the research before and during the environmental alteration, in the area of construction of the barrage of Capim Branco I. In what regards the area of construction of the barrage of Capim Branco II we are not able to reach to a conclusion once the research was held during only two months period of the construction of the barrage.